Pemaknaan Lirik Lagu Shabondama Karya Ujo Noguchi Berdasarkan Analisis Semiotika Michael Riffaterre - Fajria Noviana; Akhmad Saifudin (Universitas Dian Nuswantoro, 2020)
Shabondama is a children's song whose lyrics are composed by Ujo Noguchi. This song tells about a game of soap balloons. Interestingly, even though it tells about children's play, this song seems mysterious. There are nuances of sadness when listening to this song. The diction used has a negative connotation, unlike most other children's songs which are cheerful and use words that have a positive connotation. This is what motivates the writer's interest in examining more deeply what the real meaning is contained in the song. The semiotic theory of Riffaterre's poetry was used to study it. Through the process of heuristic reading, hermeneutic reading, and intertext studies, the result shows that the meaning contained in this song is helplessness or weakness. Keywords: semiotics, poetry, Riffaterre, semantic indirectionShabondama adalah lagu anak yang liriknya dikarang oleh Ujo Noguchi. Lagu ini menceritakan permainan balon sabun. Menariknya, meskipun bercerita tentang permainan anak namun lagu ini terkesan misterius. Ada nuansa kesedihan ketika mendengarkan lagu ini. Diksi yang digunakan pun berkonotasi negatif, tidak seperti kebanyakan lagu anak lainnya yang ceria dan menggunakan kata-kata yang berkonotasi positif. Inilah yang melatarbelakangi ketertarikan penulis untuk mengkaji lebih dalam apa makna sebenarnya yang terkandung di dalam lagu itu. Untuk mengkajinya digunakan teori semiotika puisi Riffaterre. Melalui proses pembacaan heuristik, hermeneutik, dan studi interteks, diperoleh hasil bahwa makna yang terkandung dalam lagu ini adalah ketidakberdayaan.Kata Kunci: semiotika, puisi, Riffaterre, ketidaklangsungan semantik